Phenotypic transition of tumor cells between epithelial- and mesenchymal-like state during adaptation to acidosis. Issue 16 (18th August 2019) - Zhang, Yongjun; Xu, Lili; Wang, Ping; Jian, Huanzhang; Shi, Xianghua; Jia, Min; Mo, Lijun; Hu, Zhiming; Li, Hongwei; Li, Jinlong
ABSTRACT: Acidic microenvironment is an important feature of solid tumors that contributes to malignant transformation. Low extracellular pH could promote epithelial-mesenchymal transition (EMT) thereby endowing tumor cells with higher invasive capability. However, the relation between EMT and tumor cell proliferation under long-term acidic condition is still not fully understood. Here, we show that tumor cells have undergone a phenotypic transition from EMT to mesenchymal-epithelial transition (MET) during adaptation to acidosis, and is closely related with cell proliferative state. Under early stage of acidic stress, tumor cells entered a non-cycling quiescent state with mesenchymal phenotype and expressed high level of stemness genes. Whereas, after long-term acid culture (2 months), acid-adapted cells resumed proliferating but lost mesenchymal phenotype. Further, our results show that the acid-adapted cells have distinct proliferative mechanism from non-acid cells, as the G1-S transcriptional factor E2F1 protein was not recovered in the adapted cells. Meanwhile, mini-chromosome maintenance 7 (MCM7) is shown to regulate the EMT to MET phenotypic transition, and is required for proliferation of the adapted cells under acidic condition. MCM7 Knockdown promoted mesenchymal phenotype and inhibited proliferation of the acid-adapted cells. While, MCM7 overexpression inhibited acid-induced EMT and supported tumor cell proliferation under acidic condition. Thus, our study provides evidence that tumor cells display phenotypic plasticity that allows them to survive acid stress.